Evaluation of glycosaminoglycans extract from Stichopus Vastus on inflammatory mediators and tissue healing on animal models with burn injury - Mohd Faeiz, Pauzi; Siti Norazlina, Juhari; Mohd Nikman, Ahmad; Farid, Che Ghazali; Shamsul Kamalrujan, Hassan; Wan Mohd Nazaruddin, Wan Hassan (2018)
OBJECTIVES To evaluate the effect of total sulphated glycosaminoglycan (GAG) from integument body wall of sea cucumber Stichopus vastus on inflammatory mediators and tissue healing on rodents with full thickness burn injury. METHODS Twelve male Sprague-dawley rats weighing 350-400 grams were distributed randomly into two groups. Six rats in group A received 5 ml/kg/day intra-peritoneal total sulphated GAG from S. vastus for 5 days, while control group received phosphate buffered saline (PBS). Level of IL-10 and IL-12 were measured at day 1, 6, and 12. All rats of each group were euthanized at day 12 and the tissue biopsies from the wounds were retrieved for histological examination. RESULTS The level of IL 10 revealed significantly (p=0.001) higher in sulfated GAG treated group on each observation from baseline (8.02±0.14) up to [day 6 (11.78±0.72) and day 12 (13.61±0.79)] compared to control group [day 1 (8.11±0.06), day 6 (8.55±0.28) and day 12 (8.88±0.42)]. The level of IL 12 was reduced significantly (p=0.001) in sulphated GAG treated group from baseline (1155.54±9.56) up to day 6 (1036.34±32.94) and day 12 (919.09±72.03) observation period compared to control group [day 1 (1150.53±22.85), day 6 (1273.91±68.38) and day 12 (1340.71±73.37)]. Data suggested that sulfated GAG from S. vastus integument body wall increase anti-inflammatory cytokine and reduce pro-inflammatory cytokine. Microscopic evaluation was done on day 12 and showed reduced neutrophils infiltration (p=0.001) with enhanced proliferation of fibroblasts (p=0.017) and increase in new vessels formation (p=0.001) in the sulphated GAG treated group compared to control group. CONCLUSIONS Sulphated GAG from S. vastus integument body wall has impact on the outcome of wound healing process by increasing the level of anti-inflammatory cytokine, IL-10 and reduced level of pro-inflammatory cytokine, IL-12 and positive effect on fibroblast proliferation and angiogenesis process.